Algorithms and Discrete Applied Mathematics Second International Conference, CALDAM 2016, Thiruvananthapuram, India, February 18-20, 2016, Proceedings - Govindarajan, Sathish; Maheshwari, Anil (Theoretical Computer Science and General Issues,, 2016)
This book collects the refereed proceedings of the Second International Conference on Algorithms and Discrete Applied Mathematics, CALDAM 2016, held in Thiruvananthapuram, India, in February 2016. The volume contains 30 full revised papers from 90 submissions along with 1 invited talk presented at the conference. The conference focuses on topics related to efficient algorithms and data structures, their analysis (both theoretical and experimental) and the mathematical problems arising thereof, and new applications of discrete mathematics, advances in existing applications and development of new tools for discrete mathematics.